A novel haemoglobin variant mimicking cyanotic congenital heart disease. (28th January 2016) - Abecasis, Francisco; Marques, Inês; Bento, Celeste; Ferrão, Anabela
Abstract : Screening for critical congenital heart defects in newborn babies can aid in early recognition, with the prospect of improved outcome. However, as this universal newborn screening is implemented, there will be an increasing number of false-positive results. In order to avoid multiple investigations and uncertainty, an haemoglobin (Hb) variant must be included in the differential diagnosis in otherwise well newborns with low oxygen saturation by pulse oximetry. We describe a novel fetal Hb variant (heterozygous γ-globin gene (HBG1) mutation in exon 2 c.202G>A (p.Val68Met)) identified in a newborn with positive pulse oximetry screening for congenital heart disease.